Brain Functional and Structural Alterations in Women With Bipolar Disorder and Suicidality - Guo, Huiling; Zhang, Ran; Wang, Pengshuo; Zhang, Luheng; Yin, Zhiyang; Zhang, Yifan; Wei, Shengnan; Chang, Miao; Jiang, Xiaowei; Tang, Yanqing; Wang, Fei (Frontiers in Psychiatry, 2021)
Objective: Suicide is the leading cause of death from bipolar disorder (BD). At least 25% to 50% of patients with BD will attempt suicide, with suicide rates much higher in women patients than men. It is crucial to explore the potential neural mechanism underlying suicidality in women with BD, which will lead to understanding and detection of suicidality and prevent death and injury from suicide. Methods: Brain function and structure were measured by amplitude of low-frequency fluctuation (ALFF) and gray matter volume (GMV) in 155 women [30 women with BD and a history of suicidality, 50 women with BD without suicidality, and 75 healthy controls (HC)]. The differences in ALFF and GMV across the BD with suicidality, BD without suicidality, and HC groups were investigated. Results: BD with suicidality showed signiﬁcantly increased ALFF in the left and right cuneus compared with BD without suicidality and HC groups. Moreover, the GMV in the left lateral prefrontal cortex and left cuneus in BD with suicidality were significantly lower than those in BD without suicidality and HC groups, while the GMV of the right ventral prefrontal cortex was significantly decreased in both BD with and without suicidality groups. Conclusions: This study combining functional and structural neuroimaging techniques may help to identify specific pathophysiological changes in women with BD and suicidality. Increased ALFF and less GMV in cuneus might represent the neuroimaging features of suicidality in women with BD. Investigating this potential neuromarker for suicidality in women with BD may lead to the ability to prevent suicidality.